The great dream of the warrior of chimera (Olhares, 2015)
This article describes the work of Renato Vianna on the implantation of the concept School-Theater based on a pedagogic system of integral education in which theory and practice interact mutually. An ethical system of which consists social responsibility and discipline.
Keywords: School-Theater; Actor's education; Pedagogic procedures; New School